PENGARUH MODAL USAHA DAN UPAH TENAGA KERJA TERHADAP PENYERAPAN TENAGA KERJA SERTA JUMLAH PRODUKSI PADA INDUSTRI TAS DI KECAMATAN TANGGULANGIN SIDOARJO - Adji, Ikko Prastyo; Priyono, Joko (Fakultas Ekonomi Universitas 17 Agustus 1945 Surabaya, Indonesia, 2020)
The purpose of this study was to determine the effect of working capital and labor wages on labor absorption and the amount of production in the bag industry in Tanggulangin District, Sidoarjo. This research was conducted on 165 MSME entrepreneurs of bag crafts in INTAKO, Tanggulangin District, Sidoarjo using documentation techniques. This study uses the panel data regression analysis method which is used to determine the effect of business capital, labor wages, labor absorption, and the amount of production, this panel data analysis is a combination of time series data and cross-section data. Panel data is data from the same individuals observed over a certain period. Based on the calculation results of e-views version 9.0 that the magnitude of the strength of the relationship between the independent variable and the dependent variable in model 1 shows 0.784, meaning that the variables of working capital, labor wages, and labor absorption together affect the amount of production by 78%. While the remaining 22% is caused by confounding factors, namely other variables outside the model that influence but are not included in this research model. While in model 2 it is 0.950, meaning that the variables of working capital, labor wages, and labor absorption together affect the amount of production by 95%. While the remaining 5% is caused by confounding factors, namely other variables outside the model that influence but are not included in this research model